Peningkatan Keterampilan Berbicara Melalui Metode Bercerita Siswa Kelas III SD INP Tanetea kecamatan Pa’jukukang Kabupaten Bantaeng - St. Wahidah (Jurnal Studi Guru dan Pembelajaran, 2020)
The formulation of the problem in this study is whether students' speaking skills can be improved through storytelling methods. This study aims to improve students' speaking skills and help students of class III INP Tanetea, Pa'jukukang district, Bantaeng Regency. This research uses the storytelling method. This type of research is a classroom action research conducted in 2 cycles, consisting of Initial Activities, Core Activities and final activities. Data obtained in this study include student learning outcomes taken from the provision of test telling in front of the class, the ability of teachers in managing learning taken from the observation sheet of teacher activities, student activities taken from the observation sheet of student activities. The results showed that in the first cycle of action there were 15 students who completed individually from 25 students so that the percentage of classical completeness was 60% and individual absorption was 64.28% while the results of student activity observation were 62.5% and teacher activity observations 87.5 % with enough categories. In the second cycle of action there were 22 students who were completed individually so that the percentage of classical completeness was 88% and individual absorption was 79.94% while the results of student activity observation were 87.5% and teacher observation results were 85.7% with very good category. This means that learning in cycle II has met the indicators of success so it can be concluded that the improvement of learning by using the Storytelling method can improve students' speaking skills in Indonesian subjects in class III SDP Tanetea, Pa'jukukang district, Bantaeng District.